2004
DOI: 10.1055/s-2004-829507
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis in Children

Abstract: The natural history and clinical expression of infection due to Mycobacterium tuberculosis differ substantially in children compared with adults. The natural history depends upon the age at infection and the host immune status. Children infected prior to age 4 have a very high rate of developing immediate clinical or radiographic manifestations or both, but are unlikely to develop reactivation disease in adulthood. In contrast, children infected in preadolescence or adolescence are more prone to developing mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0
14

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 83 publications
2
12
0
14
Order By: Relevance
“…Pediatric wards are often considered to be low-risk areas as children with TB are less infectious than adults [25]. However, in this sample, we found HCWs who had a history of working in pediatric wards had an increased incidence of TB.…”
Section: Discussionmentioning
confidence: 61%
“…Pediatric wards are often considered to be low-risk areas as children with TB are less infectious than adults [25]. However, in this sample, we found HCWs who had a history of working in pediatric wards had an increased incidence of TB.…”
Section: Discussionmentioning
confidence: 61%
“…The greatest number of cases occurred in the 5–14 year age group. This age category is typically defined by lower rates of TB, 8 suggesting under diagnosis in children less than five years.…”
Section: Discussionmentioning
confidence: 99%
“…These include protean clinical presentation, the limited ability of children to produce sputum, and paucity of tuberculosis bacilli in samples that are produced. 8 Because of the rapid progression from infection to clinical disease—typically in less than 12 months—there is a limited time window for clinicians to identify children at risk of exposure and those in the early stages of disease. 8,9 HIV-infected children face unique risks because of the higher rate of household exposure to TB, faster progression from infection to disease, and the high incidence of other infections that may complicate diagnosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ahidjoetal [6] reported that out of 125 children with pulmonary TB 9 were found to be having cavitary lesions given a prevalence of 7.2%. However, cavitary disease in children may result from poor containment at the site oforganism deposition in a very young and/or immune-compromised children, aspiration of live bacilli when a diseased lymphnode erupts into an airway, among those less than 5 years of age, and the third being the adulttype disease found mainly in children greater than 10 years of age [7]. Both cases presented here may have developed cavitary disease due to one of these reasons.…”
Section: Discusionmentioning
confidence: 79%